Perceptions of Managers’ Appraisal Process and their Relation to Employees Performance in a non-Western Culture: Evidence from Jordan - Alamro, Mohammad Qwaider; Ghadi, Mohammed Yasin; Al-Qatawenh, Aymn Sulieman; Farooq, Ayesha (International Review of Management and Marketing, 2017)
The aim of this study was to test a hypothesized model to examine the impact of factors surrounding performance appraisal (rater characteristics, halo, personal bias, leniency and compassion and overstatement) on dimensions of subordinates’ performance (i.e., amount of work, discipline, completion of tasks and quality of work) within the Water Authority Corporation in Jordan. The population of the study consisted of employees working in full time in the SSC. To recruit the sample a developed questionnaire was distributed randomly to 300 potential employees working in Water Authority. After careful examination, 270 responses were valid for data analysis, resulting in an overall response rate of 90%. An empirical research method was performed to extract relevant points. Application of stepwise regression analysis and correlational tests lends support to the hypotheses of the study. The results showed that the perceptions of staff in the Water Authority of the factors surrounding the process of performance evaluation were high. Also, the results revealed that perceptions of the staff at the Water Authority to the level of job performance were highly. The reported findings provide valuable insights to managers by corroborating and extending prior empirical findings in Jordan. Furthermore, the staff awareness of the effectiveness of the applied performance evaluation system in the Water Authority indicates that the presidents understand the staff problems. So they like to improve the daily relationship with the president. It also leads to enhance satisfaction with their relationship with their colleagues at work, their salaries and their relationship with the managers. So the availability of these dimensions will have a positive impact in improving the staff performance. Further implications, potential limitations and recommendations for future research are discussed. Keywords: performance appraisal, job performance, Water Authority, Jordan JEL Classification: L25